Do you reap what you sow? Driving mechanism of supply chain transparency on consumers' indirect reciprocity - He, Shaohua (Frontiers in Psychology, 2023)
To maintain sustainable poverty alleviation in the post-pandemic world, China encourages firms to participate in the "Social Commerce Helping Farmers Project." This study aims to explore the phenomenon of indirect reciprocity between firms, consumers, and farmers in the supply chain. With 860 WeChat users, an online questionnaire survey based on a random vignette-based experiment was conducted. We developed a model clarifying how supply chain transparency inspires consumers' indirect reciprocity. Partial least square analysis structural equation modeling (PLS-SEM) was used to validate our research model. Supply chain transparency of social responsibility practices asymmetrically affects three dimensions of consumer trust by improving perceived information quality. The three dimensions of trust asymmetrically contribute to indirect reciprocity. Moreover, compassion and the need for social status moderate the relationship between different variables in the model. The results indicate that supply chain transparency improves consumer trust, making consumers more responsive and rewarding companies that assist vulnerable groups in their supply chains. Faced with a trust crisis, companies can take different measures to achieve their goals based on each dimension of trust.